THE MEDIATING ROLE OF GOVERNMENT INTERNAL CONTROL IN THE RELATIONSHIP BETWEEN GOVERNANCE HUMAN RESOURCE COMPETENCE AND FINANCIAL REPORTING QUALITY - Mutiara Fadhlina; Agus Ismaya Hasanudin; Nurhayati Soleha (LPPM UNIVERSITAS BINA INSAN, 2026)
Abstract Purpose: Prior studies give mixed evidence on whether government internal control only predicts reporting quality or mediates the effect of governance and competence. This study tests internal control as an accountability conversion mechanism in a vertical public-sector organization with recurring audit issues, namely the Regional Office of the Directorate General of Corrections Banten. Research Methodology: A quantitative explanatory cross-sectional survey was conducted among financial, asset, and reporting personnel. Of 136 eligible personnel across 17 units, 117 usable responses were analyzed using PLS-SEM in SmartPLS 4. Slovin was used only to set a minimum response target for a finite population, while the study approached the full eligible population. Instrument validation used convergent validity, discriminant validity, reliability testing, pilot testing, and PLS-SEM diagnostics available in the thesis output. Results: All direct paths were positive and significant. Internal control partially mediated the effects of governance and competence on financial statement quality. The model showed strong R-square and Q-square values, f-square effects from small to large, and structural VIF values below 5. Conclusions: Financial statement quality improves when governance discipline and personnel competence are translated into risk assessment, verification, reconciliation, monitoring, and audit follow-up through internal control. Limitations: The single-site, cross-sectional, and self-reported design limits causal inference and requires careful interpretation of common method bias risk. Contributions: The study integrates Agency Theory and the Resource-Based View by positioning internal control as the mechanism that links accountability structures and strategic human resources to financial reporting quality